CHALLENGING POTENCY OF JAYENGAN : NEW OPPORTUNITY FOR DEVELOPMENT OF SUSTAINABLE JEWELRY CREATIVE INDUSTRIAL KAMPUNG-BASED TOURISM IN SURAKARTA - Winny Astuti; Qomarun Qomarun; Alpha Febela; Rufia Andisetyana Putri; Dyah Widi Astuti (Geoplanning: Journal of Geomatics and Planning, 2017)
Local-based tourism becomes one of economic development strategies of the area based on local potency. Sustainable tourism can be defined as ‘tourism, which takes into account of its current and future economic, social and environmental impacts’, addressing the demands of visitors, the environment, the industry and local communities as the host of development. KampungJayengan Surakarta is the traditional settlement located in the downtown, which spontaneously developed by Banjar Community, that arrived in Surakarta in 1746 as jewelry traders. Right now, the existence and the identity of Kampung Jayengan as Kampung of Jewelry has been lost its attraction, constrained by development of modern public facilities and services in the city center. This study analyzed the challenge faced by Kampung Jayengan to develop its potencies as Jewelry Industrial Kampung-based Tourism becoming a part of tourist destination in Surakarta as a creative city. The research type was predictive research by using mixed methods. Several analysis have been conducted from identification of the potencies of kampung. It consisted of analysis comformity of the area to the spatial structure general plan policy; analysis of demographic; analysis of economy, analysis of availability of public infrastructure; analysis of building and environment and analysis of land use suitability.  Results of analysis shows that the area has a great challenge for Jewelry Industrial Kampung-based Tourism development, which will have multiplier effect on increasing economic development of the area as well as economic development and welfare of the local community.